Investigation of the Load-Sharing Theory of the RC Pipes Rehabilitated with Slip Liners - Bai-jian Li; Liang-sheng Zhu; Xin-sha Fu (Advances in Civil Engineering)
Slip-lining is a preferred rehabilitation approach in the departments of transportation in China. Although the method is the most common rehabilitation technique, few research studies have been conducted on the mechanical behavior of a rehabilitated reinforced concrete pipe (RCP). A series of experiments were conducted on RCPs rehabilitated with a corrugated steel pipe (CSP), a steel pipe, a high-density polyethylene (HDPE) pipe, and a shape steel bracket. The RCP rehabilitated with the CSP showed an increase in both the load-carrying capacity (3.46 times greater than the RCP) and the stiffness (5.35 times greater than the RCP). The RCP rehabilitated with the steel pipe, HDPE pipe, and steel bracket exhibited an increase in the load-carrying capacity (1.23, 1.50, and 1.31 times greater than the RCP, respectively), and the stiffness of these three pipes was not markedly changed. The slip-lined pipe acts as a “pipe within a pipe” system. A “load-sharing” theory was proposed in this study and provides estimates of the load-carrying capacity of the slip-lined pipes.